The Role of School Management in Improving the Quality of Education in Indonesian Embassy Schools in the Kingdom of Saudi Arabia - Muhammad Ridho; Dr. Saud G. Albeshir (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The purpose of this research was to uncover the reality of the role of school management in improving the quality of education in Indonesian Embassy Schools in the Kingdom of Saudi Arabia. The researcher employed the descriptive survey method to achieve the study's aims and the questionnaire as a tool for the study, which consisted of 40 phrases separated into two axes (quality level and obstacles/difficulties). The study population comprised 117 administrators and teachers at Indonesian Embassy Schools in the Kingdom of Saudi Arabia. The following are some of the study's most significant findings: The study subjects agree strongly with the quality of school management in Indonesian Embassy Schools in the Kingdom of Saudi Arabia, with an average score of 4.38 out of 5. The study subjects agree to a moderate degree on the obstacles and difficulties facing school management in the quality of education in Indonesian Embassy Schools in the Kingdom of Saudi Arabia, with an average score of 2.64 out of 5. The researchers suggest that, in light of the findings, the most crucial course of action be taken: encourage cooperation between administrators and teachers by creating opportunities for teamwork and exchange of ideas and successful practices; enhance the levels of educational quality by providing continuous training programs for administrators and teachers that focus on developing their skills and updating their knowledge of the latest educational practices; promote a culture of innovation and constant improvement in the school by encouraging administrators and teachers to participate in the development and implementation of policies and improvement practices.